Zufallsbefunde in der muskuloskeletalen Radiologie - Wünnemann, Felix; Rehnitz, Christoph; Weber, Marc-André (Der Radiologe, 2017)
BackgroundIncreasing numbers of conventional X‑rays, computed tomography and magnetic resonance imaging in the inpatient, outpatient and scientific routine leads to an increasing number of incidental findings. The correct interpretation of these incidental findings with respect to the relevance and the evaluation concerning further work-up is an important task of radiologists.ObjectiveDescription of common incidental findings in musculoskeletal imaging and their clinical classification.Material and methodsA PubMed literature search was performed using the following terms: incidental findings, population-based imaging, musculoskeletal imaging, non-ossifying fibroma, enchondroma, osteodystrophia deformans, chondrosarcoma, fibrous dysplasia, simple bone cyst, unicameral bone cyst, solitary bone cyst, aneurysmal bone cyst, vertebral hemangioma, bone island, osteopoikilosis, Tarlov cyst and diffuse idiopathic skeletal hyperostosis (DISH).ResultsIncidental findings are observed in up to 40% of imaging procedures. In up to 6% these incidental findings involve the skeletal system. Common incidental findings are discussed and their clinical relevance is explained.